ISOLATION AND SCREENING OF FUNGI ASSOCIATED WITH DISEASED RIVER CATFISH, Pangasius hypophthalmus - MAT HUSIN, EQMAL MUSTAQEEM; IBERAHIM, NURUL AQILAH (Universiti Malaysia Terengganu Journal of Undergraduate Research, 2022)
The production of river catfish Pangasius hypophthalmus trade has increased significantly over the past decade. Concerning the high demand for river catfish, P. hypophthalmus, these freshwater fish are susceptible to fungi infection that can cause mortality to individual and fish eggs. This study has been conducted to identify the morphology of isolated fungi and their extracellular- enzymes for virulent screening. Three fishes with apparent signs of infection such as ulcerative, haemorrhages and dermal lesions were collected from the fish cage culture at Kampung Serada, Kuala Terengganu. Fungi were isolated from the fish externally (fin, skin, mouth, gill) and internal organs (kidney and liver). The fungal morphology was characterised macroscopically by observing the colony features such as margin, pigmentation (colour), elevation, texture and shape of fungi on an agar plate. Meanwhile, for micromorphology observation were characterised the fungi structure includes the spore, hyphae, and conidiaphore. Based on the identification using a general key to characteristics moulds, two fungi have been classified into two genera: Rhizopus-like sp and Geomyces-like sp. These fungi proceeded with extracellular enzyme tests such as the proteolysis assay, amylases test and lipases test. The reaction enzymes of fungi from the amylases test showed the clearing zone around the radial colony growth of fungi. The test strain of fungi screened during the present investigation proved to be an efficient producer of protein and polysaccharide degrading enzymes. Rhizopus-like sp and Geomyces-like sp to produce extracellular amylase enzyme indicated the virulent characteristic of the isolate and the ability of those fungi to initiate infection or resist harsh environments and treatments.